Granulosa Cell Apoptosis in the Ovarian Follicle—A Changing View - Regan, Sheena L. P.; Knight, Phil G.; Yovich, John L.; Leung, Yee; Arfuso, Frank; Dharmarajan, Arun (Frontiers in Endocrinology, 2018)
Recent studies challenge the previous view that apoptosis within the granulosa cells of the maturing ovarian follicle is a reflection of aging and consequently a marker for poor quality of the contained oocyte. On the contrary, apoptosis within the granulosa cells is an integral part of normal development and has limited predictive capability regarding oocyte quality or the ensuing pregnancy rate in IVF programmes. This review article covers our revised understanding of the process of apoptosis within the ovarian follicle, its three phenotypes, the major signalling pathways underlying apoptosis as well as the associated mitochondrial pathways.